The Role Of Figures And Institutions In The Development Of Islamic Education In The Golden Age And Its Relevance In The Modern Era - Sismidarti, Sismidarti; Amin, Alfauzan; Saepudin, Saepudin (Jurnal Kajian Ilmu Pendidikan (JKIP), 2025)
This study examines the central role of figures and institutions in the development of Islamic education during the golden age, particularly from the 8th to the 14th centuries CE, and their relevance for the renewal of Islamic education in the modern era. Using library research methods, this study traces the contributions of great scholars such as Al-Kindi, Al-Farabi, Ibn Sina, Al-Ghazali, Ibn Rushd, Al-Biruni, and Al-Khawarizmi, and examines the function of classical educational institutions including the Nizamiyah Madrasah, Al-Qarawiyyin University, and Bayt al-Hikmah in building a strong Islamic intellectual tradition. The research findings indicate that the success of Islamic education during the golden age was supported by the integration of religious and rational sciences, a strong institutional ecosystem, and a scientific ethos that respects morality and character. In the modern era, fundamental values ​​such as the integration of knowledge, character education, a holistic curriculum, and the use of technology remain highly relevant and can serve as models in responding to the challenges of globalization, digitalization, and the need for 21st-century competencies. Thus, the legacy of classical Islamic education provides a strategic foundation for strengthening a sustainable, innovative, and globally competitive Islamic education system.